THE EFFECTIVENESS OF QUIZIZZ TO IMPROVE STUDENTS' VOCABULARY : A CASE STUDY OF 7th GRADE AT SMPN 14 SEMARANG - Risma Annisa; Sri Wahyuni; Nur Hidayat (JEELL (Journal of English Education, Linguistics and Literature), 2025)
This study examines the effectiveness of Quizizz, a gamified learning platform, in improving vocabulary proficiency among seventh-grade students at SMPN 14 Semarang. A quantitative experimental design was employed with 64 students, who were allocated into an experimental group instructed via Quizizz and a control group instructed using conventional techniques. Data were gathered by pre-test and post-test vocabulary evaluations, supplemented with a student questionnaire. The validity and reliability of the instrument were established (Pearson's correlation significance < 0.05; Cronbach's Alpha = 0.718). Data analysis utilizing SPSS 26 encompassed normality assessment, homogeneity evaluation, paired sample t-tests, and independent t-tests. The results indicated that both groups exhibited improvement; however, the experimental group attained more gains (mean improvement of 9.37 points) than the control group (8.12 points). Statistical analyses revealed significant differences (Sig. 0.000 < 0.05) favoring the Quizizz group. The effectiveness of Quizizz is due to its gamification features, immediate feedback, and alignment with adolescents' learning preferences. The study suggests that Quizizz is an effective and entertaining instrument for vocabulary acquisition; however, additional research with larger samples and extended duration is advised.